Lipid Storage Myopathy in Behçet's Disease: A Rare Cause of Elevated Serum Creatine Kinases Levels. (3rd June 2012) - Yilmaz, Sedat; Cinar, Muhammet; Karslioglu, Yıldırım; Simsek, Ismail; Erdem, Hakan; Pay, Salih; Dinc, Ayhan
Abstract : Muscular involvement in Behçet's disease is rare and there are only a few case reports in the literature. The causes of elevated muscle enzymes in a patient with Behcet's disease are many, including myositis, drug-induced myopathy, metabolic myopathy, and the disease itself. We herein have defined an algorithmic approach to a patient with Behcet's disease and elevated muscle enzymes and report a case of coexisting of lipid storage myopathy.